Effect of auditory enrichment (music) in pregnant sows welfare - Silva, Flávia R.S. (2017)
Studies have shown that the benefits from music can improve the welfare conditions of laboratory, pet and production animals. The study aimed to evaluate the influence of music (Antonio Lucio Vivaldi compositions) on behavior aspects (position, activity, stereotypes, social and agonistic behavior) and physiological responses (respiratory rate and rectal temperature) in gestating sows in individual cages (stage 1), and collective stalls (stage 2). 28 animals were studied, 14 belonged to music group, and 14 to the control group (without music).The respiratory rate had the lowest averages in the group with music, for example, in stage 1, time 1, values of 19.28 and 21.50 mov.min-1. In stage 2, the values found in the same time were 20.36 and 24.16, and in time 2, values of 24.37 and 27.18 mov.min-1. These findings follow in stage 2 until time 4.Behaviors position, activity, stereotypes and agonistic interaction with the researcher were also influenced by the music. We concluded from the results that music influenced the behavior of animals, providing greater relaxing and reduce stereotypes aspects related to a better welfare.